KONTRIBUSI INVOLVEMENT DAN TRUST IN A BRAND DALAM MEMBANGUN LOYALITAS PELANGGAN - Licen Indahwati Darsono; Basu Swastha Dharmmesta (Journal of Indonesian Economy and Business (JIEB), 2005)
Customer loyalty is the most valuable asset for the company. Many researchs found thatcustomer loyalty had a positive effect on company’s profitability. The purpose of thisresearch is to investigate involvement and trust in a brand (as cognitive and conativeantecedent of loyalty) contribution to building loyalty. The object of this research is facialwhitening product, and the subjects are women. Survey has been done in two centrallocations in Yogyakarta.This research found that involvement and trust in a brand has a positive effect onrelative attitude as attitudinal dimension of loyalty, relative attitude has a positive effect on repeat patronage as behavioral dimension of loyalty. This research also found a strongsupport about relative attitude’s role as a mediator of involvement-repeat patronagerelationships and trust in a brand-repeat patronage relationships. Therefore, involvementand trust in a brand are mediated by relative attitude to contribute to bulding loyalty.Key words: involvement, trust in a brand, relative attitude, repeat patronage